Role of adiponectin in osteoarthritis - Feng, Xinyuan; Xiao, Jiaying; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is a widespread and most common joint disease which leads to social cost increasing accompany with aging population. Surgery is often the final treatment option. The major progression of OA includes cartilage degradation caused by chondrocytes metabolism imbalance. So, the molecular mechanisms of action in chondrocytes may provide insights into treatment methods for OA. Adiponectin is an adipokine with many biological functions in the cell metabolism. Numerous studies have illustrated that adiponectin has diverse biological effects, such as inhibition of cell apoptosis. It regulates various functions in different organs, including muscle, adipose tissue, brain, and bone, and regulates skeletal homeostasis. However, the relationship between adiponectin and cell death in the progression of OA needs further investigation. We elaborate the structure and function and the effect of adiponectin and state the correlation and intersection between adiponectin, autophagy, inflammation, and OA. From the perspective of oxidative stress, apoptosis, pyroptosis, and autophagy, we discuss the possible association between adiponectin, chondrocyte metabolism, and inflammatory factor efforts in OA. What’s more, we summarize the possible treatment methods, including the use of adiponectin as a drug target, and highlight the potential future mechanistic research. In this review, we summarize the molecular pathways and mechanisms of action of adiponectin in chondrocyte inflammation and death and the pathogenesis of OA. We also review the research on adiponectin as a target for treating OA. These studies provide a novel perspective to explore more effective treatment options considering the complex interrelationship between inflammation and metabolism in OA.